2018
DOI: 10.1088/1361-648x/aad102
|View full text |Cite
|
Sign up to set email alerts
|

Surface enhancement of water at the ionic liquid–gas interface of [HMIM][Cl] under ambient water vapor

Abstract: The ionic liquid-gas interface of 1-hexyl-3-methyl-imidazolium chloride, [HMIM][Cl], was examined in the presence of water vapor using lab-based ambient pressure x-ray photoelectron spectroscopy (APXPS) at room temperature. The interfacial water uptake was measured quantitatively in the pressure range of high vacuum up to a maximum of 5 Torr (27% RH) and back to high vacuum in a systematic manner. Water mole fractions in the interface determined from APXPS were compared to previously published tandem different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
3
5
0
Order By: Relevance
“…Upon introduction of water vapor, two additional peaks appear at higher BEs in the O 1s spectra due to interfacial water (O w ) at the gas−IL interface and gas phase water (O g ) that is present between the sample surface and the 0.5 mm aperture above the sample. Consistent with our previous water/IL AP-XPS studies, 46,47 these spectra do not change as a function of time, indicating that the surface water concentration does not change for a given pressure and the interfacial region is in equilibrium with gas phase water. Representative spectra of [C 4 mim][Ace] in the presence of 2.5 Torr for each isotherm are shown in Figure 1b.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Upon introduction of water vapor, two additional peaks appear at higher BEs in the O 1s spectra due to interfacial water (O w ) at the gas−IL interface and gas phase water (O g ) that is present between the sample surface and the 0.5 mm aperture above the sample. Consistent with our previous water/IL AP-XPS studies, 46,47 these spectra do not change as a function of time, indicating that the surface water concentration does not change for a given pressure and the interfacial region is in equilibrium with gas phase water. Representative spectra of [C 4 mim][Ace] in the presence of 2.5 Torr for each isotherm are shown in Figure 1b.…”
Section: Resultssupporting
confidence: 90%
“…The interfacial region shows a consistently higher water mole fraction relative to the bulk. We have observed previously in a room temperature isothermal study of [C 6 mim]­[Cl] via AP-XPS that water is enhanced at the interface when compared to bulk absorption . This behavior of water enhancement at the IL interface relative to the bulk has also been observed by MD simulations of [C 1 mim]­[Cl]. , The difference in the observed x w at the gas–IL interface compared to the bulk in Figure c suggests that the thermodynamics of water varies as it crosses the [C 4 mim]­[Ace] gas–liquid interface during absorption and evaporation under equilibrium conditions.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Rivera-Rubero and Baldelli, for example, showed that water can be removed from the IL 1-butyl-3-methylimidazolium tetrafluoroborate ([C 4 C 1 Im]­[BF 4 ]) at pressures of <1 × 10 –5 mbar at room temperature . The recent availability of near-ambient pressure XPS (NAPXPS) has opened up the possibility of measurements of liquid surfaces in gas pressures of up to a few tens of mbar. ,, In our own work and in works of groups such as the Newberg group, NAPXPS has allowed for surface-sensitive studies of the interactions between gas molecules and ILs. Herein, we examine the reaction of the superbasic IL, [P 66614 ]­[benzim], with CO 2 , H 2 O, and two mixed CO 2 /H 2 O vapor regimes using NAPXPS.…”
Section: Introductionmentioning
confidence: 90%
“…An Ag/AgCl is used as a QRE in order to appropriately control the WE. Recently, our group has utilized APXPS to examine IL/gas interfaces in the presence of water vapor [63–66] . Herein these studies are extended by examining the IL 1‐butyl‐3‐methyimidazolium acetate, [C 4 mim][OAc], as a function of water vapor pressure and external bias.…”
Section: Introductionmentioning
confidence: 99%